Ge-doped silica optical fibre for Time Resolved Radiation Dosimetry. (December 2021) - Basaif, A.; Oresegun, Adebiyi; Tarif, Zubair H.; Zin, Hafiz; Choo, K.Y.; Ibrahim, S.A.; Abdul-Rashid, H.A.; Bradley, D.A.
Abstract: Time-resolved radiation dosimetry in radiotherapy helps determine the quality of delivery of patient prescribed doses. Earlier reports on doped silica optical fibres as scintillators in radioluminescence (RL) based radiation dosimetry have indicated particular merits, including versatility, robustness, high spatial resolution, wide dynamic range, and the ability for real-time measurements. Time-resolved radiation dosimetry requires high temporal resolution, enabled using a suitable scintillator and high-speed electronics. We report on the potential of Ge-doped optical fibres as a suitable scintillator to be adopted for use in a time-resolved radiation dosimetry system. High-energy clinical X-ray beams (6 MV) were used to irradiate the Ge-doped optical fibre samples. RL responses were recorded for six dose-rates (between 100 MU/min and 600 MU/min) delivered by a Varian 2100 C/D linear accelerator. The photon-counting circuit gating time was set at its shortest capability of 100 μs? The Ge-doped optical-fibre scintillator showed linear RL response, with minimal observable memory and afterglow and plateau effects. The fluorescence lifetime analysis, demonstrate a calculated rise time of 590.1 ns and a decay time of 0.423 μs, indicating superior performance compared to other scintillator forms. These results demonstrate the potential for the Ge-doped optical-fibre scintillator to be used in a time-resolved radiation dosimetry system. Highlights: Manuscript Number: RPC-D-21-00446. Ge-doped Silica Optical Fiber for Time Resolved Radiation Dosimetry. Time-resolved radiation dosimetry at 100 μs gating time using Ge-doped Silica Optical Fiber as a scintillator. Linear response with minimal observable memory and afterglow and plateau effects. The fluorescence lifetime analysis, demonstrate a calculated rise time of 590.1 ns and a decay time of 0.423 μs.